2022
DOI: 10.1021/acsami.2c10338
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Porous Inorganic Structures via Block Copolymer Lithography: An Application of the Versatile and Selective Infiltration of the “Inverse” P2VP-b-PS System

Abstract: A facile and versatile strategy was developed to produce highly ordered porous metal oxide structures via block copolymer (BCP) lithography. Phase separation of poly(2vinylpyridine)-b-polystyrene (P2VP-b-PS) was induced by solvent vapor annealing in a nonselective solvent environment to fabricate cylindrical arrays. In this work, we thoroughly analyzed the effects of the film thickness, solvent annealing time, and temperature on the ordering of a P2VP-majority system for the first time, resulting in "inverse" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…Through the contact of the BCP thin film with chloroform vapors, i.e., a nonselective solvent, unfavorable interactions between the P2VP (poly 2-vinylpyridine) and the PS blocks can be reduced, which leads to the vertical alignment along the surface plane of the domains. 32 Therefore, based on the two molecular weights studied in this work, different morphologies were obtained. Figure 1C presents topographical atomic force microscopy (AFM) images of the self-assembled polymeric thin films with the PS cylinders of varying dimensions, i.e., diameters of about 32 and 343 nm, being embedded within the P2VP matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the contact of the BCP thin film with chloroform vapors, i.e., a nonselective solvent, unfavorable interactions between the P2VP (poly 2-vinylpyridine) and the PS blocks can be reduced, which leads to the vertical alignment along the surface plane of the domains. 32 Therefore, based on the two molecular weights studied in this work, different morphologies were obtained. Figure 1C presents topographical atomic force microscopy (AFM) images of the self-assembled polymeric thin films with the PS cylinders of varying dimensions, i.e., diameters of about 32 and 343 nm, being embedded within the P2VP matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Phase separated P2VP- b -PS films were prepared according to previous studies. , Silicon wafers were cut into 4 cm 2 squares and subjected to ultrasonic cleaning in acetone for 20 min, followed by drying with a stream of N 2 . Solutions of BCP1 (1.5 wt %) and BCP2 (2.0 wt %) were prepared in a 1:4 mixture of toluene and tetrahydrofuran.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It is also important to point out that solvent inclusion dramatically changes phase diagrams. Because of this, great care is needed to ensure that the swelling can be controlled enough to allow the various morphology changes to be properly controlled avoiding more random and poorly ordered films. ,, Chloroform was chosen as the solvent because it can swell both blocks but has preferential affinity for the minority P4VP block. Experimental evidence has also shown chloroform’s preference for interacting with the P4VP block .…”
Section: Resultsmentioning
confidence: 99%
“…However, to achieve the porous pattern, they used a microphase separated PEO- b -PS BCP thin film, where PS, not PEO, is the cylinder forming phase and PEO is the majority block. In a study carried out by Esmeraldo Paiva et al, they also demonstrated the fabrication of vertically aligned pores on the substrate using P2VP- b -PS BCP, where again PS, not P2VP is the cylinder forming phase and P2VP is the majority block. However, forming continuous oxide films with vertical pores is less well demonstrated despite their potential use in, for example, sensor and diagnostic tests because of their high surface area and size selectivity.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, block copolymer aided nanostructuring can be combined with traditional techniques such as lithography, resulting in block copolymer lithography. Paiva et al 94 following similar strategy were able to obtain highly ordered porous metal oxide structure packed as 40 nm diameter cylinders, which can be used diodes, and integrated circuits. Additionally, it provides the possibility of selective infiltration with metal cations offering high fidelity metal oxide structures.…”
Section: Applicationsmentioning
confidence: 99%